ERA 2012 Versus ERA 2010: Like the Curate's Egg … Good in Parts. (June 2015) - Crowe, Simon F; Samartgis, Jodi
<x xml:space="preserve">Abstract</x> Objective The Excellence in Research for Australia (ERA) assessment exercises undertaken in 2010 and 2012 were developed by the Australian Research Council (ARC) with the aim of identifying and promoting excellence in research across the full spectrum of research activity in Australia's higher education institutions. Method Three fields of research are relevant to psychology and are denoted by the following codes: 1701 (psychology), 1702 (cognitive sciences), and 1799 (other psychology and cognitive sciences), as well as the combination of these, 17 (psychology and other cognitive sciences). In the first analysis of these data, all academic organisational units (AOUs) were compared across year (i.e., ERA 2010 and ERA 2012). The second analysis involved an examination of differences between AOUs in each of the 2010 and 2012 ERA data collections. Finally, the third analysis compared AOUs by the major groupings of universities that have emerged in the sector. Results The comparison of the 2010 and 2012 data collections reveals an overall improvement in performance with most universities improving or at least holding their ground. Conclusion It is concerning that a sizeable component of the production arising from the institutions reveals that only nearly half of the institutions meet a benchmark of at or above world standard. Some reasons for this performance are discussed, and suggestions are made for areas for improvement in the performance of the discipline going forward.